Optimizing the Size of Public Road Contracts - Iimi, Atsushi; Benamghar, Radia (World Bank, Washington, DC, 2012)
Procurement packaging has important effects on not only the bidders' bidding behavior, but also contractors' performance. By changing the size of public contracts, procurers can encourage (or discourage) market competition and improve contract performance, avoiding unnecessary cost overruns and project delays. In practice, there is no single solution about how to package public contracts. With procurement data from road projects in Nepal, this paper examines the optimal size of road contracts in rural areas. The optimum varies depending on policy objectives. To maximize the bidder participation, the length of road should be about 11 kilometers. To minimize cost overruns and delays, the contracts should be much larger at 17 and 21 kilometers, respectively. Compared with the current procurement practices, the findings suggest that procurers take more advantage of enlarging road packages, although contracts that are too large may increase the risk of discouraging firms from participating in public tenders.